FOXP2 gene and language impairment in schizophrenia: association and epigenetic studies - Moltó María D; Dagnall Adam M; Sanjuán Julio; Tolosa Amparo; Herrero Neus; de Frutos Rosa (BMC, 2010)
Abstract Background Schizophrenia is considered a language related human specific disease. Previous studies have reported evidence of positive selection for schizophrenia-associated genes specific to the human lineage. FOXP2 shows two important features as a convincing candidate gene for schizophrenia vulnerability: FOXP2 is the first gene related to a language disorder, and it has been subject to positive selection in the human lineage. Methods Twenty-seven SNPs of FOXP2 were genotyped in a cohort of 293 patients with schizophrenia and 340 controls. We analyzed in particular the association with the poverty of speech and the intensity of auditory hallucinations. Potential expansion of three trinucleotide repeats of FOXP2 was also screened in a subsample. Methylation analysis of a CpG island, located in the first exon of the gene, was performed in post-mortem brain samples, as well as qRT-PCR analysis. Results A significant association was found between the SNP rs2253478 and the item Poverty of speech of the Manchester scale (p = 0.038 after Bonferroni correction). In patients, we detected higher degree of methylation in the left parahippocampus gyrus than in the right one. Conclusions FOXP2 might be involved in the language disorder in patients with schizophrenia. Epigenetic factors might be also implicated in the developing of this disorder.